Development of the knowledge of fertility and fertility preservation scale - McNees P; Cho J; Azuero A; Meneses K; Jukkala A (Dove Medical Press, 2012)
Angela Jukkala1, Karen Meneses1, Andres Azuero1, June Cho1, Patrick McNees1,21School of Nursing, 2School of Health Professions, University of Alabama at Birmingham, Birmingham, AL, USAObjective: Infertility is a severe and often underestimated consequence of successful treatment for breast cancer. Ensuring young breast cancer survivors receive patient-centered health information on the impact of treatment on fertility and fertility preservation options in a timely manner is a critical component of high quality nursing care. The objective of this manuscript is to report the process used to develop and examine the reliability and validity of an instrument to measure a breast cancer survivor’s self-assessed knowledge of fertility and fertility preservation.Design: A scale development and descriptive study.Setting: Online and global.Participants: Ninety-two young breast cancer survivors (ages 25–45 years).Methods: Participants completed the Knowledge of Fertility and Fertility Preservation (KF) Scale as part of their participation in a larger study, the Fertility Cancer Project (FCP).Results: An exploratory factor analysis revealed five domains: normal reproductive function; general information about fertility; cancer treatment factors affecting fertility; infertility information; and alternative parenting options. A confirmatory factor analysis confirmed the validity of the construct with a demonstrated good fit between the factor structure of the new scale and the observed data. Many participants self-assessed their overall knowledge of fertility and fertility preservation as “a little” and the majority rated their knowledge of infertility information as “a little”.Conclusion: The KF Scale can be used to provide useful information to support health care professionals in the development of patient-centered education that is responsive to the unique needs of each young breast cancer survivor. The initial testing of the KF Scale indicates that it is reliable and easy to use; however, additional testing with larger and more diverse groups of breast cancer survivors is needed to further determine reliability and validity. The KF Scale could also be examined as a possible measure of self-assessed knowledge of fertility and fertility preservation across diverse groups of young cancer survivors, such as survivors of Hodgkin’s disease or childhood leukemia.Keywords: knowledge of fertility, knowledge of fertility and fertility preservation scale, Fertility Cancer Project